O dialogismo e a construção de sentido nas cartas encíclicas do papa Bento XVI - Branco, Nanci Moreira (2012)
This study aims to analyze how the dialogical relationships and construction of meaning are built in current Catholic religious discourse, here represented by the encyclical letters of Pope Benedict XVI. I understand that even a discourse as established as the religious it is influenced by several others with which they share and to which they oppose ideas or use them to establish the meaning of the discourse. Thus, the dialogism and construction of meaning will be observed in the clash that occurs between the texts of the pope and the present discourses in society in different contexts, explicity and implicity referred to by the author, or even the discourses that are formed in different contexts in which these themes are inserted. So, the developed analysis will seek to understand, from the observation of dialogism in the documents in question, how to organize such discursive genre, and then establish, from the undeniable formation of extraverbal on the verbal, which is the relationship they have with these texts that circulate in society. I therefore consider that dialogical relations enable convergence or divergence, acceptance or refusal. In that way, one must do the question: what kind of opposing discourses should they keep deleted to preserve the hegemony of the official discourse? Which discourses are confronted with it? A discourse that intends to be dominant it tends to exclude others, not belonging to their universe that are not accepted or are discredited. The fundamental question of this analysis is therefore to understand the discourses of which we must defend and discourses to which we must resort to form the intended meaning in the encyclical letters in Authier Revuz (1990): that another one needs to defend, the other is needed to resort to be formed (p.31). Hence, this analysis seeks to verify how it happens, in the language, the confrontation of ideas which constitutes the discourse of this letter, analyzing how the voice of the Other is part of such discourse. The thought that will guide this research will be based on studies of the Russian philosopher Milkhail Bakhtin on Dialogism and Ideology.